MENGINGAT PENGALAMAN MINORITAS: NARASI SUNYI PENGALAMAN PELADANG PEREMPUAN : (Kajian Pustaka Program Food Estate Kalimantan Tengah) - Evi Nurleni (Prodi Sosiologi FISIP UPR, 2021)
Development and modernity are concepts that a positivist perspective, which views both humans and the universe as materials that can be utilized for the benefit of securities or economic security, example the food estates program which are seen as post-pandemic national food security. In the structure of the political economy, the narrative of local experiences and women cultivators becomes silent in conversation because they are not in accordance with the interests of development and modernity. The silent narrative of the experience of women cultivators in the perspective of historical materialism seeks to critically place women’s narratives in the patriarchal system and capitalism. The history of women’s experiences is the history of minority groups (herstory); which. shows that they are a minority group as a non-working class in the patriarchal concept, and materialist in the capitalist concept. Women become objects of development and minority groups whose voices are never heard. In this case, efforts to reformulate the women’s empowerment movement must be carried out without creating antagoni sm. The search for a way without antagonism is carried out by formulating the philosophy of the minority as a narrative materialism herstory in a socialist and radical feminist approach.